Preoperative evaluation of ovarian masses with color Doppler and its correlation with pathological finding - Khurana, Isha; Satia, Meena N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Most ovarian cancers are diagnosed in advanced stages because these tumours may not cause any specific symptoms, particularly in its early stages. Though specific risk actors have been identified there are no reliable screening tests for ovarian cancer. However, improvements in identification of women at high risk for ovarian cancer, as well as improved imaging techniques like the USG and color Doppler along with CT Scan and MRI has increased the likelihood of early detection. Methods: The aim of the study was to evaluate the efficacy of color and spectral Doppler in diagnosing the ovarian malignancy. A Prospective randomised study was conducted at a tertiary care centre where 50 patients with ovarian masses were selected. The study design included thorough history taking and clinical examination followed by evaluation of tumour markers. USG along with color Doppler evaluation was done followed by surgery and then co-related with histopathology. The color Doppler parameters such as vascularity, distribution of vascularity, pulsatility and resistive index were also evaluated and statistical significance assessed. Results: Color Doppler showed increased vascularity in 100% of malignant tumors in contrast to only 54.24% of benign tumors. Absent blood flow in a solid tumor almost always ruled out the possibility of malignancy. Spectral Doppler helped to assess the nature of the blood vessels picked up on color Doppler. All the patients in the malignant group and 4 patients in the borderline group had PI<1.0. Remaining 6 tumors with P1 <1.0 belonged to the benign group. Out of 15 patients with PI >1.0, 13 were benign and 2 patients had borderline tumours. RI of <0.4 was seen in 8 Patients with malignancy and RI of >0.4 was seen in 26 patients with benign lesions. Conclusions: Color Doppler is a good non-invasive modality to differentiate benign from malignant lesions. Vascularity is most sensitive and RI is most specific. Thus, color Doppler and spectral Doppler tremendously increased the reliability in diagnosing a malignant ovarian tumor. Color Doppler served as an important tool to rule out malignancy in solid tumors if they failed to show any intra-tumoral vascularity. B-Mode USG in combination with color Doppler and spectral Doppler is proposed as the first and foremost diagnostic modality in patients with ovarian tumor, so as to establish the definite diagnosis of malignancy early in the course of the disease.